The making of a market : credit, henequen, and notaries in Yucatán, 1850-1900 - Levy, Juliette, 1968- (Pennsylvania State University Press, 2012)
During the nineteenth century, Yucatán moved effectively from its colonial past into modernity, transforming from a cattle-ranching and subsistence-farming economy to a booming export-oriented agricultural economy. Yucatán and its economy grew in response to increasing demand from the United States for henequen, the local cordage fiber. This henequen boom has often been seen as another regional and historical example of overdependence on foreign markets and extortionary local elites. In The Making of a Market, Juliette Levy argues instead that local social and economic dynamics are the root of the region's development. She shows how credit markets contributed to the boom before banks (and bank crises) existed and how people borrowed before the creation of institutions designed specifically to lend. As the intermediaries in this lending process, notaries became unwitting catalysts of Yucatán's capitalist transformation. By focusing attention on the notaries' role in structuring the mortgage market rather than on formal institutions such as banks, this study challenges the easy compartmentalization of local and global relationships and of economic and social relationships.